Hubungan Tingkat Stress Dengan Indeks Prestasi Pada Mahasiswa Semester Akhir Program Studi Farmasi Fakultas Farmasi Dan Ilmu Kesehatan Universitas Sari Mutiara Indonesia - Sri Ramadhani; Indomora Siregar (Departement of Mathematics Education, 2024)
This study aims to identify the relationship between stress levels and grade point average in final semester students of the pharmacy study programme at Sari Mutiara University of Indonesia. The research method used was quantitative with descriptive approach and associative analysis. Data collection was done through questionnaires to 56 respondents. The results showed that there was a relationship between stress level and achievement index, but the relationship was categorised as low with a significant value = 0,149 > 0,05 from the correlation test results. Nonetheless, this finding confirms that stress can affect students' grade point average through decreased concentration and ability to complete academic activities. Therefore, universities and study programmes need to pay attention to the factors that cause stress and take steps to manage students' stress so that they can achieve optimal academic performance.